2005
DOI: 10.1016/j.devcel.2005.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO Pathway Is Essential for Nuclear Integrity and Chromosome Segregation in Mice

Abstract: Covalent modification by SUMO regulates a wide range of cellular processes, including transcription, cell cycle, and chromatin dynamics. To address the biological function of the SUMO pathway in mammals, we generated mice deficient for the SUMO E2-conjugating enzyme Ubc9. Ubc9-deficient embryos die at the early postimplantation stage. In culture, Ubc9 mutant blastocysts are viable, but fail to expand after 2 days and show apoptosis of the inner cell mass. Loss of Ubc9 leads to major chromosome condensation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
416
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(439 citation statements)
references
References 53 publications
21
416
1
1
Order By: Relevance
“…Only recently, Ubc9-deficient mice have been described. However, because of early lethality of mutants shortly after implantation, studies had to be carried out with cultured blastocystes (Nacerddine et al, 2005). Here, we report ubc9 loss-of-function studies in intact zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently, Ubc9-deficient mice have been described. However, because of early lethality of mutants shortly after implantation, studies had to be carried out with cultured blastocystes (Nacerddine et al, 2005). Here, we report ubc9 loss-of-function studies in intact zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout studies in mouse have revealed multiple roles of Ubc9 required for proper nuclear function in proliferating cells of the early embryo, such as regulation of overall nuclear organization, chromosome segregation, and nucleocytoplasmic transport (Kuehn, 2005;Nacerddine et al, 2005). In comparison, chondrocyte precursors in ubc9.1 morphants appear to have rather specific defects.…”
Section: Loss Of Ubc9 Leads To Compromised Mitosis and Cellular Overgmentioning
confidence: 99%
See 1 more Smart Citation
“…Bien que la séquence primaire de SUMO soit différente de celle de l'ubiquitine, la structure tridimensionnelle de ces deux protéines est similaire (Figure 1). La sumoylation est un processus essentiel puisque l'invalidation des enzymes de la sumoylation est délétère pour les cellules eucaryotes [2,3]. Le terme SUMO regroupe une famille de 4 protéines (SUMO1-4), formées chacune d'environ 100 résidus.…”
Section: Qu'est-ce Que La Sumoylation ?unclassified
“…Additionally, sumoylation targets promyelocytic leukemia (PML) and the homeodomain-interacting protein kinase 2 (HIPK2) to specific domains within the nucleus [27]. By knocking out the essential E2 conjugating Ubc9 enzyme, the sumoylation pathway iwas shown to be essential for nuclear integrity and normal segregation of chromosomes [28].…”
Section: Ccaat Enhancer Binding Protein Alpha (C/ebpα)mentioning
confidence: 99%